Faktor-Faktor yang Memengaruhi Cash Holding Sebelum dan Selama Pandemi COVID-19 - Yanti, Alfredo Suwito, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to analyze the effect of liquidity, profitability, firm size, leverage, and capital expenditure on cash holding before and during the COVID-19 pandemic, and differences in average cash holding. Based on purposive sampling there are 94 manufacturing companies during 2019 representing pre-pandemic condition and 2020 representing condition during the pandemic. Hypothesis testing with regression analysis and Wilcoxon signed-rank test using SPSS 26. Research before the pandemic shows profitability, leverage, and capital expenditure have a significant effect on cash holding, while liquidity and firm size have insignificant effect on cash holding. Research during the pandemic shows that liquidity, leverage, and capital expenditure have a significant effect on cash holding, while profitability and firm size have insignificant effect on cash holding. Study finds significant differences between average cash holding before and during the pandemic, so this result supports the precautionary-motive for saving money amid the pandemic.